Impact of Deep Breathing, Murottal, and Hypertension Exercises on Headache Management in Hypertensive Individuals - Stia Pusporini, Lenny; Alifiani , Herna; Islamiah, Imas (Journal of Current Health Sciences, 2024)
Hypertension, characterized by an abnormal increase in blood pressure, often triggers headaches at the back of the head and neck due to vascular disturbances. This study explores the effectiveness of a holistic non-pharmacological intervention—comprising Deep Breathing Relaxation Technique, Qur'anic recitation (murottal), and Hypertension Exercise—to alleviate these headaches in hypertensive patients at Mekarjaya Community Health Center, Indonesia. Employing a quantitative approach, the research utilized a Quasi-Experimental Design with a Pretest and Posttest Control Group. The intervention group underwent IMAS therapy, an integrated approach combining the three techniques, while the control group continued only with routine medication. Conducted in December 2022 with 16 participants in each group, results from both Dependent and Independent T-tests (p < 0.05) confirmed the significant effect of the interventions. This study not only underscores the potential of such integrative therapies in managing hypertension-related headaches but also contributes to broader health care practices by offering a viable alternative to conventional medication. The findings align with and extend existing research on relaxation therapies for hypertension, suggesting substantial benefits in patient well-being and symptom management.